1987
DOI: 10.1002/ajh.2830250309
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of von willebrand factor in thrombosis following asparaginase‐prednisone‐vincristine therapy for leukemia

Abstract: To determine if factor VIII-von Willebrand factor (vWF) complex is involved in the thrombosis associated with asparaginase-prednisone-vincristine induction therapy for acute lymphoblastic leukemia, plasma vWF was analyzed by sodium dodecyl sulfate-agarose gel electrophoresis and crossed immunoelectrophoresis. Five patients with cerebral thrombosis were studied; all had a decreased platelet count following the complication. Sequential studies of three patients disclosed changes in plasma vWF multimer pattern. O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
22
0

Year Published

1988
1988
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(22 citation statements)
references
References 21 publications
0
22
0
Order By: Relevance
“…[2][3][4][5][6][7][8][9][10][11][12][13][14] However, the true prevalence and extent of TEs in this patient population are unknown. The PARKAA Study was an open, randomized, controlled, extended, Phase II study with the primary objective of determining the prevalence of TEs in children with ALL during treatment with ASP.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[2][3][4][5][6][7][8][9][10][11][12][13][14] However, the true prevalence and extent of TEs in this patient population are unknown. The PARKAA Study was an open, randomized, controlled, extended, Phase II study with the primary objective of determining the prevalence of TEs in children with ALL during treatment with ASP.…”
Section: Discussionmentioning
confidence: 99%
“…The timing of TEs in children with ALL is very consistent in the literature, occurring either during or immediately after chemotherapy with L-asparaginase (ASP). [2][3][4][5][6][7][8][9][10][11][12][13][14] ASP is an effective chemotherapeutic agent that catalyzes the hydrolysis of L-asparagine. Human lymphoblasts rely on exogenous asparagine, and ASP induces a relative asparagine deficiency, resulting in cell death.…”
mentioning
confidence: 99%
“…Pui et al 7,16 demonstrated in 1985 and 1987 that an altered von Willebrand factor molecule was found in leukemic children treated with CASP and PRED. Therefore, we have included the determination of von Willebrand factor antigen in the study presented here.…”
Section: Discussionmentioning
confidence: 99%
“…The fact that the iatrogenic damage induced by L-Ase on the hemostatic system is not due to AT III synthesis alone, but also to other factors in the hemostatic balance was confirmed, however [13]. The administration of AT III concentrates alone surely cannot restore hemostasis.…”
Section: Discussionmentioning
confidence: 89%